Pelaksanaan Program Tahfiz Al-Qur’an Dalam Penanaman Karakter Santri di Pesantren Daarutahfiz - Asy’ari, Irfan; Trisno, Bambang (Indonesian Research Journal on Education, 2023)
Education is expected to be able to spearhead the progress of this nation, but in reality until now it has not been fully realized. The education that is important to instill is character education, becausecharacter education should be taught from an early age. Character education in the formation of the personality of students through the Al-Qur'an tahfiz program at the Daaru Tahfiz Cinangkiak Islamic boarding school, Batu Taba, Agam Regency. Through case study research by means of observation it was found that the implementation of the tahfiz program was an attempt to instill the character of the students.The method used in the tahfiz of the Qur'an for the Daaru Tahfiz Islamic boarding school is to use the tikrar method. The tikrar method is a method of memorizing tahfiz by reading it repeatedly until it is memorized. The tahfiz program aims to foster and develop the abilities of students as students in memorizing the Qur'an and to instill the character of students.